Front Cover: Structural States of Hdm2 and HdmX: X‐ray Elucidation of Adaptations and Binding Interactions for Different Chemical Compound Classes (ChemMedChem 14/2019). (17th July 2019) - Kallen, Joerg; Izaac, Aude; Chau, Suzanne; Wirth, Emmanuelle; Schoepfer, Joseph; Mah, Robert; Schlapbach, Achim; Stutz, Stefan; Vaupel, Andrea; Guagnano, Vito; Masuya, Keiichi; Stachyra, Therese‐Marie; et al.
Abstract : The Front Cover shows a crystal of HdmX in a drop of mother liquor and the X‐ray structures of the clinical trial compounds NVP‐CGM097 and NVP‐HDM201 bound to Hdm2. The article reveals key structural states of the cancer target proteins Hdm2 and HdmX. Elucidation of the binding interactions for different chemical classes of inhibitors and of the sometimes surprising protein adaptations was key in the design and optimization of these inhibitors. For HdmX, a key crystallization additive is revealed, which enabled the determination of high‐resolution structures. Taken together, these new X‐ray findings (nine new structures for Hdm2, HdmX, and the previously unpublished details for eight Hdm2 complexes) should prove to be useful for the design and optimization of further selective or dual inhibitors. More information can be found in the Communication by Joerg Kallen, Pascal Furet et al. on page 1305 in Issue 14, 2015 (DOI: 10.1002/cmdc.201900201 ).